Experimental Evaluation of the Deposition Dynamics of Different Petroleum Blends in a Benchtop Heat Exchanger Test Instrument - Villardi, H. G. D.; de Medeiros, F. F.; Orrico, L. C.; de Souza, A. L. B.; Junior, I. M.; Liporace, F. S.; Pessoa, F. L. P. (Energies (Basel), 2023)
The article delves into the intricate phenomenon of deposition in heat exchangers and how a piece of equipment known as the benchtop heat exchanger test instrument (BHETI) has been developed to expedite the examination of this phenomenon. The BHETI subjects samples to substantial stress, facilitating the assessment of an oil’s tendency to generate deposits. Tests were conducted on two crude oil blends referred to as blend A and blend B using a BHETI unit. This equipment permits testing under various controlled conditions, including temperature, pressure, and volumetric flow rate. The results indicated that blend A exhibited a higher susceptibility to deposition compared to blend B due to its elevated concentration of light hydrocarbons. The wall temperature exerted a significant influence on the deposition rate, with higher temperatures leading to elevated deposition rates. Conversely, lower oil flow rates resulted in increased deposition rates. Furthermore, extended-term tests unveiled fluctuations in deposition rates over time when blending the two oil samples, suggesting intermittent fouling processes, possibly attributable to thermodynamic imbalances induced by mixing, rendering the oil’s asphaltenes less stable. The outcomes were subjected to analysis employing the Colloidal Instability Index (CII), which indicated that the majority of samples exhibited values exceeding 0.9, signifying asphaltene instability. Additionally, the examination of saturated, aromatic, and NSO (nitrogen, sulfur, oxygen) fractions revealed decreased saturation and increased aromatics after the deposition tests.